2013
DOI: 10.1016/j.jebo.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic footprints in organizational behavior

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…It is argued that this significant shift laid the economic basis for revolutionary changes, including the institutional change (Richerson et al, 2003) that manifested cooperation in anonymous large systems. Existing prior to the agricultural system, the structure of hunter-gatherer societies as described by Boehm (1993) was egalitarian, in contrast to the central polities of contemporary societies where the power of decision-making is delegated to a relatively steady, institutionalized leadership (see also Lee & Daly, 1999;Witt & Schwesinger, 2013). Boehm's (1993) evolutionary theory suggests that in hunter-gatherer societies individuals had substantial autonomy, a considerable voice in community affairs, and could enforce fair, responsive behavior in their leaders (Boehm, 1993;Richerson et al, 2003).…”
Section: Decentralized Structurementioning
confidence: 99%
See 2 more Smart Citations
“…It is argued that this significant shift laid the economic basis for revolutionary changes, including the institutional change (Richerson et al, 2003) that manifested cooperation in anonymous large systems. Existing prior to the agricultural system, the structure of hunter-gatherer societies as described by Boehm (1993) was egalitarian, in contrast to the central polities of contemporary societies where the power of decision-making is delegated to a relatively steady, institutionalized leadership (see also Lee & Daly, 1999;Witt & Schwesinger, 2013). Boehm's (1993) evolutionary theory suggests that in hunter-gatherer societies individuals had substantial autonomy, a considerable voice in community affairs, and could enforce fair, responsive behavior in their leaders (Boehm, 1993;Richerson et al, 2003).…”
Section: Decentralized Structurementioning
confidence: 99%
“…The researchers posit that these factors both increase group member commitment when a task is assigned (especially when assigned by consensus, and facilitate the development of an attitude for which accomplishing the assigned tasks is a major element of reward. Ambivalence toward behavior traits tied to self-interest motives can still disrupt this process by degrading the motivational mechanism that enables such decentralized structures (Witt and Schwesinger, 2013 Lerner and Tirole (2002): Why would thousands of top-notch software developers contribute for free to the creation of a public good? Through extensive research conducted in this field, scholars have identified the dominant role of self-interest motivation as determining contributions to OSS.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cladistics is the classification method developed in biology to hypothesise relationships between organisms. This method is widely applied to non-biological systems, including the study of language (Rexová et al ., 2006), business (Goumagias et al ., 2014), organisational behaviour (Witt & Schwesinger, 2013) and other fields.…”
Section: Cladistics Analysismentioning
confidence: 99%
“…12 However, some bio-economists argue that the capacity to behave in these ways is also a product of genetically inherited factors. See, for example, Witt and Schwesinger (2013). 13 Mokyr (2002) the novelty involved ensures that there is uncertainty.…”
Section: Complex Economic Systemsmentioning
confidence: 99%